2018
DOI: 10.18203/2394-6040.ijcmph20180255
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable disease risk factor profile among Fishermen community of Kancheepuram district, Tamil Nadu: a cross sectional study

Abstract: Background: Owing to growing epidemic of non communicable diseases (NCD), identification of risk factor profile is one of the high-priority actions required in reducing NCDs. Further, fishermen community possesses unique characteristics of a folk society despite the urban environment around it. Since major portion of the life of fishermen is spent at sea with bizarre sleep and eating pattern, their risk profile for non-communicable disease are different from general population. The objectives of the study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
3
14
0
Order By: Relevance
“…An Indonesian cross-sectional study also showed waist circumference was associated with blood glucose levels [37]. Higher salt intake was associated with higher prevalence of hypertension in coastal rural communities in India [38, 39]. The most recent Malaysian nationally representative data (MANS 2014) on nutrient intake showed that the indigenous population in Sabah had a higher median sodium intake (2026 mg) compared to the national median (1935 mg) [40].…”
Section: Discussionmentioning
confidence: 99%
“…An Indonesian cross-sectional study also showed waist circumference was associated with blood glucose levels [37]. Higher salt intake was associated with higher prevalence of hypertension in coastal rural communities in India [38, 39]. The most recent Malaysian nationally representative data (MANS 2014) on nutrient intake showed that the indigenous population in Sabah had a higher median sodium intake (2026 mg) compared to the national median (1935 mg) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of cigarattes/bedis/cigars smoked was 5 per day which was almost similar to the result obtained in a study done among the fishermen community of Kancheepuram district of Tamil Nadu. 14 The minimum recommended consumption of fruits and vegetables is 5 servings of each per week. 12 59.3% of individuals consumed ≥5 servings of fruits per week and 85.2% of them consumed ≥5 servings of vegetables which was remarkably high compared to other studies done in different parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…They further reported fisheries addicted to bidi/cigarette and liquor were 11% and 65% respectively and 10% in both bidi/cigarette and liquor 16 . Study in Tamil Nadu by Annadurai et al (2018) pointed out that among the fisheries 17.1% were smoking tobacco user and 22.9% smokeless tobacco user 27,28 . Kadam (2015) showed that smoking, betel-nut chewing and alcohol consumption in fishermen community are common habits 15 .…”
Section: Alcohol and Tobacco Addictionmentioning
confidence: 99%
“…Their study also showed that fluorosis had high in aged and male fisheries among tobacco and alcohol addicted group 36 . Study by Annadurai et al (2018) revealed that hypertension had l39.05% due to high intake of salt from dry fish intake 27 .…”
Section: Morbidity Patternmentioning
confidence: 99%
See 1 more Smart Citation